Clinical experience with two etanercept biosimilars in Indian patients with spondyloarthritis - Ashok Kumar; Anshul Goel; Mehul Lapsiwala; Mohit Goyal; Gaurav Dembla (Indian Journal of Rheumatology)
Background: Antitumor necrosis factor (TNF) drugs are highly efficacious in spondyloarthritis (SpA). We present retrospective analysis of our experience with 2 etanercept biosimilars (Etacept and Intacept). Methods: Clinical record of patients with axial and/or peripheral SpA (Assessment of SpA International Society [ASAS] criteria) registered during April 2013–September 2016 was retrieved. Those with active disease (Bath Ankylosing Spondylitis Disease Activity Index [BASDAI] >4), despite 1-month trial of two non-steroidal anti-inflammatory drugs (NSAIDs) (axial) and/or 3-month trial of disease modifying anti-rheumatic drugs (peripheral), received anti-TNF therapy. Etanercept biosimilar (50 mg) was administered weekly for the first 12 weeks. Patients achieving “major improvement” after 12 weeks (Ankylosing Spondylitis Disease Activity Score [ASDAS] reduction by >2 points) received the dose every 2 weeks subsequently. BASDAI, Bath Ankylosing Spondylitis Functional Index, and ASDAS and NSAID index were noted at baseline, 12, and 24 weeks. For Etacept, week 52 and 104 data were also available. Primary endpoint was BASDAI <4 at 12 weeks. Results: Males constituted the majority (76%) and mean ASDAS was 4.7. In patients receiving Etacept, BASDAI <4 and major improvement were achieved by 12 weeks in 77% (42/54) and 61% (33/54) patients, respectively. Forty-three patients had completed 52 weeks and 27 patients had completed 104 weeks of treatment. Among 27 patients completing 104 weeks, secondary end points: ASAS 20, 40, and ASAS-partial remission status were achieved by 89%, 67%, and 41%, respectively. Intacept results were available up to 24 weeks and were comparable to those of Etacept. Injection site reactions followed by upper respiratory tract infections were the most common adverse reactions. One patient developed tuberculous pleural effusion. Conclusion: Etanercept biosimilar therapy was found efficacious and safe.